Burnout, COVID-19, social support and food insecurity in health workers - Colichi, Rosana Maria Barreto [UNESP]; Bernardo, Larissa Cassiano [UNESP]; Dias Baptista, Simone Cristina Paixão [UNESP]; Fonseca, Alan Francisco [UNESP]; Weber, Silke Anna Theresa [UNESP]; Lima, Silvana Andrea Molina [UNESP] (Acta Paulista de Enfermagem, 2023)
Objective: To evaluate the prevalence of risk for Burnout Syndrome among health professionals in areas of care for patients with COVID-19, as well as to verify possible associations of the syndrome with the perceived social support and food insecurity of these workers. Methods: Analytical cross-sectional study, with workers from intensive care units (ICU) and wards caring for patients with COVID-19, in a university hospital. Data collection was carried out from September to October 2021, using the instruments: Maslach Burnout Inventory (MBI-HSS), Multidimensional Perceived Social Support Scale and Food Insecurity Experience Scale (FIES). Statistical analysis used Poisson regression models and multiple Poisson regression, considering statistically significant differences and associations if p<0.05. Results: A total of 75 workers from three wards (48%) and from one ICU (52%) participated in the survey, and the professionals are mostly female (89.3%), trained as health care technicians (66.7%). Regarding the risk of Burnout Syndrome, 26.7% of the workers had scores for at least one dimension of the scale, mainly referring to high emotional exhaustion (20%). There was a positive association between the risk of developing Burnout Syndrome and food insecurity (PR = 1.11; 95%CI = (1.04; 1.18); p = 0.002). The number of children was significantly negatively associated with the incidence of Burnout Syndrome (PR = 0.90; 95%CI = (0.83; 0.97); p = 0.008). Conclusion: Positive associations were observed with a higher risk of BS in professionals with food insecurity and also that the number of children acts as a protective factor against the risk of Burnout Syndrome, which may be directly related to perceived social support.
Keywords: Burnout professional; Food security; Health personnel; Pandemics; Social support